2012
DOI: 10.1016/j.fsi.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression specificity of the mussel antifungal mytimycin (MytM)

Abstract: a b s t r a c tWe previously reported the nucleotide sequences and diversity of mytimycin (MytM) from the Mediterranean mussel, Mytilus galloprovincialis. Using real-time PCR (q-PCR), we observed that the MytM gene was mainly expressed in circulating hemocytes and to a less extent in the mantle. In vivo challenge with bacteria or with the yeast, Candida albicans, did not increase the expression as measured by q-PCR in hemocytes. By contrast, injection of the filamentous fungus, Fusarium oxysporum, induced a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…By contrast, the IMD pathway is similar to the tumor-necrosis-factor (TNF) receptor pathway of mammals (Ferrandon et al, 2007;Hoffmann, 2003). After AMPs were discovered in bivalves (reviewed by , regulation of their transcription levels in response to experimental immune stimulation was reported in the Mediterranean mussel, Mytilus galloprovincialis (Mitta et al, 1999a(Mitta et al, ,b, 2000bSonthi et al, 2012;Venier et al, 2011), the deep-sea hydrothermal vent mussel, Bathymodiolus azoricus (Bettencourt et al, 2007), the Pacific oyster, Crassostrea gigas (Gonzalez et al, 2007;Gueguen et al, 2006;Schmitt et al, 2012), the carpet-shell clam, Ruditapes decussatus (Gestal et al, 2007), the hard clam, Mercenaria mercenaria (Perrigault et al, 2009), the triangle-shell pearl mussel, Hyriopsis cumingii (Ren et al, 2011) and the blue mussel, Mytilus edulis (Tanguy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the IMD pathway is similar to the tumor-necrosis-factor (TNF) receptor pathway of mammals (Ferrandon et al, 2007;Hoffmann, 2003). After AMPs were discovered in bivalves (reviewed by , regulation of their transcription levels in response to experimental immune stimulation was reported in the Mediterranean mussel, Mytilus galloprovincialis (Mitta et al, 1999a(Mitta et al, ,b, 2000bSonthi et al, 2012;Venier et al, 2011), the deep-sea hydrothermal vent mussel, Bathymodiolus azoricus (Bettencourt et al, 2007), the Pacific oyster, Crassostrea gigas (Gonzalez et al, 2007;Gueguen et al, 2006;Schmitt et al, 2012), the carpet-shell clam, Ruditapes decussatus (Gestal et al, 2007), the hard clam, Mercenaria mercenaria (Perrigault et al, 2009), the triangle-shell pearl mussel, Hyriopsis cumingii (Ren et al, 2011) and the blue mussel, Mytilus edulis (Tanguy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported antifungal peptides from sea lamprey (Petromyzon marinus) plasma (Rose & Durth, 2009) and protein compounds from mussel species Mytilus galloprovincialis (Sonthi et al, 2012) and Crenomytilus grayanus (Chikalovets et al, 2015). Based on this, the compounds responsible for the antifungal activity observed in the fractions from anchovy viscera, might be of protein or peptide nature, which possible were not appropriately extracted with the procedure used in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…Mussels, fungus, in vivo challenge and sampling Adult mussels, M. galloprovincialis (6e7 cm shell length) from Palavas (Mediterranean Sea-France), filamentous fungus, F. oxysporum, injection and hemocyte collection 9h post-injection corresponding to maximum MytM expression, were as previously reported [24]. Posterior adductor muscle have been dissected 9h after injection, immediately immerged in liquid nitrogen and grounded into 1 ml of Trizol.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported on polymorphism of the antifungal peptide mytimycin (MytM) from the Mediterranean mussel, Mytilus galloprovincialis, with the existence of 16 nucleotide sequences translated into 6 amino acid sequences [23]. Among various challenges with bacteria and fungi, only injection of Fusarium oxysporum was able to increase the mytm gene expression with maximum expression observed 9h post-challenge, as measured on pools of hemocytes from 10 mussels [24]. In addition to such analyses performed on pools, the present report focused on the expression of MytM gene in individual M. galloprovincialis, before and after injection with the filamentous fungus, F. oxysporum.…”
Section: Introductionmentioning
confidence: 99%